2000
DOI: 10.1152/jn.2000.84.1.401
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Tetrode Spike Separation as Determined by Simultaneous Intracellular and Extracellular Measurements

Abstract: Simultaneous recording from large numbers of neurons is a prerequisite for understanding their cooperative behavior. Various recording techniques and spike separation methods are being used toward this goal. However, the error rates involved in spike separation have not yet been quantified. We studied the separation reliability of "tetrode" (4-wire electrode)-recorded spikes by monitoring simultaneously from the same cell intracellularly with a glass pipette and extracellularly with a tetrode. With manual spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,010
4
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,049 publications
(1,033 citation statements)
references
References 43 publications
16
1,010
4
3
Order By: Relevance
“…Wood et al (2004) have reported an average of 23% false positives and 30% false negatives for manual spike sorting of synthetic datasets performed by experts using commercial software. Harris et al (2000) have obtained similar estimates using simultaneous intracellular recording to determine the true firing pattern of neurons. Practical automated spike sorting applications must strike a balance between maximizing accuracy and maintaining low computational complexity.…”
Section: Introductionmentioning
confidence: 83%
“…Wood et al (2004) have reported an average of 23% false positives and 30% false negatives for manual spike sorting of synthetic datasets performed by experts using commercial software. Harris et al (2000) have obtained similar estimates using simultaneous intracellular recording to determine the true firing pattern of neurons. Practical automated spike sorting applications must strike a balance between maximizing accuracy and maintaining low computational complexity.…”
Section: Introductionmentioning
confidence: 83%
“…Spike sorting was performed with the Klustakwik software suite (Harris et al 2000). Putative GABAergic fast-spiking neurons (expressing ChR2) were identified on the basis of their action potential (AP) waveforms and auto-correlograms.…”
Section: (B) Experiments II -Cortical Stimulation and Inhibitionmentioning
confidence: 99%
“…There are several methods available (Xu and Wunsch, 2010) for this that include but are not limited to: k-means clustering (Chan et al, 2008), Bayesian clustering (Dai et al, 2008), valley detection (Kim and McNames, 2007;Mahmud et al, 2012), superparamagnetic clustering (Quiroga et al, 2004), expectation maximization (Harris et al, 2000;Pouzat et al, 2002) and artificial neural networks (ANN). k-means is one of the most frequent utilised in offline sorting (Gibson et al, 2012).…”
Section: Clustering Algorithmsmentioning
confidence: 99%
“…2b), we used PCA features (Harris et al, 2000). This is because this dataset has a high level of environmental noise and separation via FSDE features deteriorates with high levels of white noise.…”
Section: Ham Clustering On Realistic Neural Signalsmentioning
confidence: 99%
See 1 more Smart Citation